Making and Breaking the Gods : Christian Responses to Pagan Sculpture in Late Antiquity - Kristensen, Troels Myrup (Book collections on Project MUSE., 2013)
The basic premise of the book at hand is that there is meaning to be 'excavated' (in both meanings of the word) from Christian responses to pagan sculpture in the period from the fourth to the sixth century. More than mindless acts of religious violence by fanatical mobs, these responses are revelatory of contemporary conceptions of images and the different ways in which the material manifestations of the pagan past could be negotiated in Late Antiquity. Statues were important to the social, political and religious life of cities across the Mediterranean, as well as part of a culture of representation that was intricately bound to bodily taxonomies and visual practices